The biblical basis and historical development of the Catholic teaching on indulgences - Godlewski, Karol Kajetan (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
Curently in The Catholic Church are spread many of spiritual pracitices in order to release human from consequences of his sins and strenghthening him in fidelity to Gospel. Some of this practices haven’t got theological and dogmatical basis. For this reason reminding about indulgences is very important. Indulgences aren’t incomprehensible relic of history or piously religious practice. They are well-established in theology and tradition form of reaching for saving fruits of Christ’s death and ressurection. Effectiveness of indulgences in person who is disposed to obtaining indulgence is guaranted by Pope’s authority of „binding and solving” (Matt. 16). This is demonstrated in this article, which consists of three chapters: The concept of indulgence, The biblical conditions of indulgences, and The history of indulgences theology.